A Facile Synthetic Approach for Cu(OH)2-Cu2O Heterostructure: A Stable Catalyst for Pollutant Degradation. Issue 2 (3rd April 2021) - Kottappara, Revathi; Palantavida, Shajesh; Vijayan, Baiju Kizhakkekilikoodayil
Abstract : In the present study, we report the development of morphologically different copper and Cu(OH)2 -Cu2 O nanostructures by a single step chemical reduction method using ascorbic acid as environmental friendly reducing agent. Morphology and crystallographic patterns of the synthesized samples were analyzed using X-ray diffraction and scanning electron microscopy. Determination of catalytic performance of both copper and Cu(OH)2 -Cu2 O nanostructure towards hydrogenation reduction of para nitrophenol and para nitroaniline using sodium borohydride as the reducing agent suggested that Cu(OH)2 -Cu2 O nanostructure is comparatively efficient in hydrogenating the nitro aromatic compounds. The improved hydrogenation capacity was suggested to be due to the formation of an in-situ composite of Cu2 O-Cu during the time of reduction reaction. Analysis on the degradation capacity of developed samples for methyl orange degradation using sodium borohydride as the reducing agent indicated significantly high reduction rate for Cu(OH)2 -Cu2 O nanostructure with a rate constant value of 0. 819 min -1, which is higher than many of the previously reported values. GRAPHICAL ABSTRACT: UF0001